Model Blended Learning : Alternatif Pembelajaran Anak Usia Dini di Masa Pandemi Covid-19 - Hijriyani, Yuli Salis; Saprialman, Saprialman (GENIUS: Indonesian Journal of Early Childhood Education, 2021)
The world of education has always been a concern of the government during the Covid-19 pandemic. One of the proofs is by urging the public to carry out online learning to prevent the spread of the Covid-19 virus. This applies to institutions at all levels of education, including early childhood education. The implementation of online learning is considered not too effective in the learning process in early childhood, and blended learning began to be an alternative in early childhood learning during pandemics. Blended learning is a learning strategy that combines online and face-to-face learning. This article aims to reveal the learning model in the face of the Covid-19 pandemic outbreak with a blended learning model. Research methods using literature studies (Literature studies), data collection is done by looking for information through written documents, photographs, images, and electronic documents that support the study activities of several books, literature, and scientific papers related to research. Data analysis used is content analysis, then conducted assessment related to blended learning, so as to get data in the form of descriptive narratives about this research. The results showed that the blended learning model could be used as an alternative solution in implementing an effective early childhood learning model in the covid-19 pandemic. A blended learning model that carries the combination of two methods, namely offline/face to face methods and online methods. In evaluation activities, that can be done using two aspects of assessment, namely on aspects of skills (for evaluation in offline learning methods) and on aspects of knowledge (for evaluation on online learning methods). Both aspects of the assessment can be compiled and combined so as to get the final value in the early childhood learning assessment process.   Abstrak Dunia pendidikan tak luput menjadi sorotan perhatian pemerintah selama masa pandemi covid-19, salah satunya yakni dengan mengimbau pembelajaran di sekolah dilaksanakan secara daring untuk sementara demi mencegah penyebaran virus covid-19. Ini berlaku bagi lembaga di semua jenjang pendidikan, termasuk pendidikan anak usia dini. Pelaksanaan pembelajaran daring dinilai belum terlalu efektif dalam proses pembelajaran pada anak usia dini dan blended learning mulai menjadi alternatif dalam pembelajaran anak usia dini saat pandemi. Blended learning merupakan strategi pembelajaran yang memadukan antara pembelajaran online dan tatap muka (offline). Artikel ini bertujuan untuk mengungkapkan model pembelajaran dalam menghadapi wabah pandemi covid-19 dengan model blended learning. Metode penelitian menggunakan studi literatur, pengumpulan data dilakukan dengan mencari informasi melalui dokumen-dokumen tertulis, foto-foto, gambar, maupun dokumen eletronik yang mendukung kegiatan telaah beberapa buku, literatur, dan karya tulis ilmiah yang berkaitan dengan penelitian. Analisis data yang digunakan adalah analisis isi, selanjutnya dilakukan pengkajian yang berkaitan dengan blended learning, sehingga mendapatkan data berupa narasi deskriptif tentang penelitian ini. Hasil penelitian menunjukkan bahwa model blended learning yang dapat dijadikan sebagai alternatif solusi dalam menerapkan model pembelajaran bagi anak usia dini yang efektif di masa pandemi covid-19. Model blended learning yang mengusung penggabungan dua metode yaitu metode luring/tatap muka dan metode daring. Pada kegiatan evaluasi yang dapat dilakukan menggunakan dua aspek penilaian yaitu pada aspek keterampilan (untuk evaluasi pada metode pembelajaran luring) dan pada aspek pengetahuan (untuk evaluasi pada metode pembelajaran daring). Dari kedua aspek penilaian tersebut dapat dikompilasi dan digabung, sehingga mendapatkan nilai akhir pada proses penilaian pembelajaran anak usia dini.